Impact of the mitochondria-targeted antioxidant MitoQ on hypoxia-induced pulmonary hypertension. Issue 3 (8th March 2018) - Pak, Oleg; Scheibe, Susan; Esfandiary, Azadeh; Gierhardt, Mareike; Sydykov, Akylbek; Logan, Angela; Fysikopoulos, Athanasios; Veit, Florian; Hecker, Matthias; Kroschel, Florian; Quanz, Karin; Erb, Alexandra; et al.
Increased mitochondrial reactive oxygen species (ROS), particularly superoxide, have been suggested to mediate hypoxic pulmonary vasoconstriction (HPV), chronic hypoxia-induced pulmonary hypertension and right ventricular remodelling. We determined ROS in acute and chronic hypoxia, and investigated the effect of the mitochondria-targeted antioxidant MitoQ under these conditions. The effect of MitoQ or its inactive carrier substance, decyltriphenylphosphonium, on acute HPV (1% O2 for 10 min) was investigated in isolated blood-free perfused mouse lungs. Mice exposed to chronic hypoxia (10% O2 for 4 weeks) or after banding of the main pulmonary artery were treated with MitoQ or decyltriphenylphosphonium (50 mg·kg −1 ·day −1 ). Total cellular superoxide and mitochondrial ROS levels were increased in pulmonary artery smooth muscle cells but decreased in pulmonary fibroblasts in acute hypoxia. MitoQ significantly inhibited HPV and acute hypoxia-induced rise in superoxide concentration. ROS was decreased in pulmonary artery smooth muscle cells, while it increased in the right ventricle after chronic hypoxia. Correspondingly, MitoQ did not affect the development of chronic hypoxia-induced pulmonary hypertension but attenuated right ventricular remodelling after chronic hypoxia as well as after pulmonary arterial banding. Increased mitochondrial ROS of pulmonary artery smooth muscle cells mediate acute HPV, but not chronic hypoxia-induced pulmonary hypertension. MitoQ may be beneficial under conditions of exaggerated acute HPV. The mitochondria-targeted antioxidant MitoQ attenuates acute hypoxic pulmonary vasoconstriction and RV remodelling, but not chronic hypoxia-induced PH http://ow.ly/PCCU30hSJKK